Coating film protective coat material and acrylic coating composition
Patent Information
- Application Number
- JP2022072652
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-18
- Filing Date
- 2022-04-26
- Publication Date
- 2025-02-06
AI Technical Summary
Existing methods for protecting coating films on non-flat objects with complex shapes, such as automobile outer panels, face challenges in efficient application and proper adhesion of protective sheets, leading to potential peeling and insufficient workability, while liquid protective films lack a base material and exhibit poor workability.
A coating film protective coating material formed from an acrylic coating composition with specific monomer ratios and properties, including acrylonitrile, provides excellent releasability and peeling workability, and can be applied using a slot die for efficient formation.
The acrylic coating composition ensures effective protection of coating films by allowing easy removal without damage, maintaining film integrity during temperature changes, and providing robust peeling properties even at high temperatures.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to a protective coating material for paint films and an acrylic coating composition. [Background technology]
[0002] A technique is known for protecting coatings on articles with coatings (for example, painted automobiles and their parts, or painted steel sheets and their molded products) by attaching a protective sheet to the coating to prevent damage to the coating during transport, storage, curing, and application. A coating protective sheet used for this purpose generally has the form of a single-sided adhesive sheet with a substrate (support substrate) having an adhesive (also called a pressure-sensitive adhesive; the same applies hereinafter) layer on one side. It is configured to achieve its protective purpose by being attached to the object to be protected via the adhesive. After fulfilling its protective role, the coating protective sheet is removed (re-peeled off) from the object. Patent Document 1 is an example of a technical document relating to coating protective sheets. [Prior art documents] [Patent Documents]
[0003] [Patent Document 1] Japanese Patent Publication No. 2011-111552 [Patent Document 2] Japanese Patent Publication No. 2004-224874 [Overview of the Initiative] [Problems that the invention aims to solve]
[0004] However, for non-planar objects to be protected (especially those with complex three-dimensional shapes, such as the body panels of automobiles), it is difficult to improve the efficiency of properly applying the protective coating sheet to the object. If the protective coating sheet is not properly applied to the object to be protected, for example, if it is applied with wrinkles, wind may blow into these wrinkles during storage or transport of the object after application, causing the protective coating sheet to peel off and failing to fulfill its intended protective purpose.
[0005] On the other hand, it has also been proposed to directly apply a liquid composition for forming a protective film onto the coating of the object to be protected, and then dry the liquid composition on the coating to form a protective film. Patent document 2 is an example of a document relating to this type of technology. However, unlike the protective sheets for coatings described above, protective films formed from liquid compositions in this way do not have a substrate, and therefore tend to lack peelability and workability when removed from the coating after they have served their protective purpose.
[0006] Therefore, the present invention aims to provide a coating protective coating material formed from a liquid coating composition, which has good peelability and ease of removal when removed from a coating film. Another related objective is to provide a coating composition suitable for forming the above-mentioned coating protective coating material and a method for forming the above-mentioned coating protective coating material. [Means for solving the problem]
[0007] According to this specification, a protective coating material (hereinafter sometimes abbreviated as "coating material") formed from an acrylic coating composition containing an acrylic polymer as a base polymer is provided. The monomer component constituting the above acrylic polymer is a monomer (m) whose homopolymer has a glass transition temperature (Tg) of 90°C or higher. T ) and monomers (m) whose homopolymer Tg is -30°C or lower. L ) and the above monomer (m T ) contains at least acrylonitrile. The above monomer component (m T) and the above monomer (m L ) and the molar ratio (m T / m L ) is 0.8 or more and 1.5 or less. The above coating material has a storage elastic modulus at 23 °C (hereinafter, may be referred to as "G’(23)") of 150 MPa or more and 1000 MPa or less, and a storage elastic modulus at 70 °C (hereinafter, may be referred to as "G’(70)") of 0.40 MPa or more. According to such a coating film protection coating material, good peelability from the coating film and good peeling workability can be exhibited.
[0008] According to this specification, there is provided an acrylic coating composition (hereinafter, may be abbreviated as "coating composition") for forming a coating film protection coating material, the coating composition having a storage elastic modulus at 23 °C of 150 MPa or more and 1000 MPa or less, and a storage elastic modulus at 70 °C of 0.40 MPa or more for forming a coating film protection coating material. The above coating composition contains an acrylic polymer as a base polymer. The monomer component constituting the above acrylic polymer includes a monomer (m T ) having a Tg of the homopolymer of 90 °C or more, and a monomer (m L ) having a Tg of the homopolymer of -30 °C or less. Here, the above monomer (m<000001)0>) contains at least acrylonitrile. The molar ratio (m T ) of the above monomer (m L ) to the above monomer (m T / m L ) in the above monomer component is 0.8 or more and 1.5 or less. According to such a coating composition, a coating film protection coating material showing good peelability from the coating film and good peeling workability can be formed.
[0009] In some embodiments of the technologies disclosed herein (including the coating protective coating materials, acrylic coating compositions, coating protective methods, etc. disclosed herein; the same applies hereinafter), it is preferable that the acrylic polymer has a glass transition temperature (hereinafter also referred to as "calculated Tg") calculated based on the composition of the monomer components, which is between -30°C and -5°C. Using an acrylic polymer with a calculated Tg within the above range makes it easier to obtain a coating protective coating material that satisfies the above-mentioned G'(23) and G'(70).
[0010] In some preferred embodiments, the acrylonitrile content in the monomer component is greater than 50 mol%. This makes it possible to realize a coating material that achieves a better balance between good peelability from the coating and good peelability.
[0011] In some embodiments of the technology disclosed herein, the coating composition may further contain 1 to 60 parts by weight of inorganic powder per 100 parts by weight of the acrylic polymer. A protective coating material formed from a coating composition of such composition can block light such as ultraviolet rays with the inorganic powder, thereby suppressing photodegradation of the protective coating material itself and the coating film protected by the protective coating material. The inorganic powder preferably contains titanium dioxide.
[0012] The above coating composition may be an aqueous emulsion in which an acrylic polymer is dispersed in an aqueous solvent. Such aqueous emulsion-type coating compositions are preferred from the viewpoint of environmental hygiene and are suitable, for example, for suppressing the amount of organic solvent used and emitted.
[0013] This specification provides a method for protecting a coating film, comprising: preparing a coating composition containing an acrylic polymer as a base polymer; applying the coating composition onto a coating film on an object to be protected; and drying the coating composition to form a coating protective coating material that temporarily protects the coating film. The monomer component constituting the acrylic polymer is a monomer (m) whose homopolymer Tg is 90°C or higher. T ) and monomers (m) whose homopolymer Tg is -30°C or lower. L ) includes the above monomer (m T ) contains at least acrylonitrile. The above monomer component (m T ) and the above monomer (m L ) molar ratio (m T / m L The ratio is between 0.8 and 1.5. According to the above coating protection method, the coating can be properly protected by the above coating protective coating material. Furthermore, according to the above coating protective coating material, good peelability and good peelability from the coating can be achieved.
[0014] In some preferred embodiments, the coating composition is applied by a slot die. By drying the slot die-coated coating composition, a protective coating material can be efficiently formed on the coating film.
[0015] In some embodiments of the technology disclosed herein, the coating composition is preferably such that the viscosity V1 measured by a BH-type viscometer at 2 rpm is 20 Pa·s or more and 200 Pa·s or less. Furthermore, the coating composition is preferably such that the shear rate measured by a cone-plate rheometer at 100 sec is 20 Pa·s or more and 200 Pa·s or less. -1 It is preferable that the viscosity V2 is 1.0 Pa·s or higher. The coating composition exhibiting the above viscosity characteristics has coating properties suitable for slot die coating. Therefore, it can be preferably used in a manner in which it is slot die coated onto a coating film of an object to be protected, and by drying the composition, a protective coating material can be efficiently formed on the coating film.
[0016] Furthermore, combinations of the elements described herein may also be included within the scope of the invention for which patent protection is sought in this application. [Brief explanation of the drawing]
[0017] [Figure 1] This is a schematic cross-sectional view showing an example of an object protected by the coating protective material according to the present invention. [Figure 2] This is a block diagram showing one embodiment of the coating protection method according to the present invention. [Modes for carrying out the invention]
[0018] Preferred embodiments of the present invention are described below. Matters other than those specifically mentioned herein that are necessary for carrying out the present invention can be understood by those skilled in the art based on the teachings on carrying out the invention described herein and the common technical knowledge at the time of filing. The present invention can be carried out based on the contents disclosed herein and the common technical knowledge in the art. In the following drawings, components and parts that perform the same function may be denoted by the same reference numeral and described accordingly, and redundant explanations may be omitted or simplified. Furthermore, the embodiments shown in the drawings are schematic representations for the purpose of clearly illustrating the present invention and do not necessarily accurately represent the size or scale of the actual product provided.
[0019] In this specification, "acrylic polymer" means a polymer of monomer components containing at least one monomer selected from the group consisting of monomers having at least one (meth)acryloyl group in one molecule and (meth)acrylonitrile. Hereinafter, monomers having at least one (meth)acryloyl group in one molecule and (meth)acrylonitrile are collectively referred to as "acrylic monomers." Therefore, in this specification, acrylic polymers are defined as polymers containing monomer units derived from acrylic monomers. A typical example of an acrylic polymer is a polymer in which the proportion of acrylic monomers among the monomer components constituting the acrylic polymer is more than 50% by weight (preferably more than 70% by weight, for example more than 90% by weight).
[0020] Furthermore, in this specification, "(meth)acryloyl" comprehensively refers to acryloyl and methacryloyl. Similarly, "(meth)acrylate" comprehensively refers to acrylate and methacrylate, "(meth)acrylic" comprehensively refers to acrylic and methacrylic, and "(meth)acrylonitrile" comprehensively refers to acrylonitrile and methacrylonitrile.
[0021] <Acrylic polymer> The acrylic coating compositions in the technologies disclosed herein contain an acrylic polymer as a base polymer. Here, "base polymer" refers to the component that accounts for more than 50% by weight (typically 70% by weight or more, for example 90% by weight or more, and may also be 95% by weight or more, or 100% by weight) of the polymer contained in the acrylic coating composition. The same meaning applies to the base polymer in protective coating materials.
[0022] The monomer component constituting the above-mentioned acrylic polymer contains at least acrylonitrile. By including acrylonitrile in the monomer component, it becomes easier to realize a coating protective material and an acrylic coating composition capable of forming such a coating material that achieve a good balance between peelability and ease of removal from the coating film. Other monomers that may be included in the monomer component are not particularly limited and can be appropriately selected to obtain the desired coating protective material.
[0023] Alkyl (meth)acrylates are one preferred example of monomers other than acrylonitrile that may be included in the monomer component. Depending on the type and amount used, alkyl (meth)acrylates can be useful for adjusting the storage modulus, tensile properties, and SP value, as described later. Alkyl (meth)acrylates can be used individually or in combination of two or more types.
[0024] As the alkyl (meth)acrylate, for example, a compound represented by the following formula (1) can be suitably used. CH2=C(R 1 )COOR 2 (1) Here, in equation (1) above, R 1 R is a hydrogen atom or a methyl group. 2 This refers to a chain-like alkyl group having 1 to 20 carbon atoms. Hereafter, this range of carbon atoms will be referred to as "C 1-20 It is sometimes expressed as "[...]". The above chain-like alkyl group may be linear or branched.
[0025] R 2 C 1-20Specific examples of alkyl(meth)acrylates, which are chain-like alkyl groups, are not particularly limited, but include, for example, methyl(meth)acrylate, ethyl(meth)acrylate, propyl(meth)acrylate, isopropyl(meth)acrylate, n-butyl(meth)acrylate, isobutyl(meth)acrylate, s-butyl(meth)acrylate, t-butyl(meth)acrylate, pentyl(meth)acrylate, isopentyl(meth)acrylate, hexyl(meth)acrylate, heptyl(meth)acrylate, 2-ethylhexyl(meth)acrylate, octyl( Examples include meth)acrylate, isooctyl(meth)acrylate, nonyl(meth)acrylate, isononyl(meth)acrylate, decyl(meth)acrylate, isodecyl(meth)acrylate, undecyl(meth)acrylate, dodecyl(meth)acrylate, tridecyl(meth)acrylate, tetradecyl(meth)acrylate, pentadecyl(meth)acrylate, hexadecyl(meth)acrylate, heptadecyl(meth)acrylate, octadecyl(meth)acrylate, nonadecyl(meth)acrylate, eicosyl(meth)acrylate, etc.
[0026] The monomer components constituting acrylic polymers may include monomers other than alkyl (meth)acrylates, in addition to acrylonitrile monomers. Some examples of such monomers include carboxyl group-containing monomers, hydroxyl group (OH group)-containing monomers, acid anhydride group-containing monomers, amide group-containing monomers, amino group-containing monomers, epoxy group-containing monomers, cyano group-containing monomers, keto group-containing monomers, monomers having nitrogen atom-containing rings, alkoxysilyl group-containing monomers, imide group-containing monomers, and other functional group-containing monomers. Appropriate use of functional group-containing monomers can enhance the cohesive strength of acrylic polymers. Functional group-containing monomers can also be useful in adjusting the storage modulus, tensile properties, and SP value, as described later.
[0027] Examples of carboxyl group-containing monomers include acrylic acid (AA), methacrylic acid (MAA), carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid. Among these, AA and MAA are preferred. Examples of hydroxyl group-containing monomers include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; polypropylene glycol mono(meth)acrylate; and N-hydroxyethyl (meth)acrylamide. Among these, hydroxyalkyl (meth)acrylates in which the alkyl group has 2 to 4 carbon atoms in a linear chain are particularly preferred as hydroxyl group-containing monomers. Examples of monomers containing an amide group include (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-butyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methylolpropane(meth)acrylamide, N-methoxymethyl(meth)acrylamide, and N-butoxymethyl(meth)acrylamide. Examples of amino group-containing monomers include aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, and t-butylaminoethyl (meth)acrylate. Examples of monomers having an epoxy group include glycidyl (meth)acrylate, methylglycidyl (meth)acrylate, and allyl glycidyl ether. Examples of cyano group-containing monomers include methacrylonitrile and 2-cyanoethyl (meth)acrylate. Examples of keto group-containing monomers include diacetone(meth)acrylamide, diacetone(meth)acrylate, vinyl methyl ketone, vinyl ethyl ketone, allyl acetacetate, and vinyl acetacetate. Examples of monomers having a nitrogen atom-containing ring include N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, N-vinylmorpholine, N-vinylcaprolactam, and N-(meth)acryloylmorpholine. Examples of monomers containing an alkoxysilyl group include 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, and 3-(meth)acryloxypropylmethyldiethoxysilane. Examples of imide group-containing monomers include cyclohexylmaleimide and isopropylmaleimide.
[0028] The monomer components constituting the acrylic polymer may include other copolymer components other than the monomers mentioned above for purposes such as improving cohesiveness. Examples of other copolymer components include vinyl ester monomers such as vinyl acetate, vinyl propionate, and vinyl laurate; aromatic vinyl compounds such as styrene, substituted styrene (α-methylstyrene, etc.), and vinyltoluene; cycloalkyl (meth)acrylates such as cyclohexyl (meth)acrylate, cyclopentyl (meth)acrylate, and isobornyl (meth)acrylate; aromatic ring-containing (meth)acrylates such as aryl (meth)acrylate (e.g., phenyl (meth)acrylate), aryloxyalkyl (meth)acrylate (e.g., phenoxyethyl (meth)acrylate), and arylalkyl (meth)acrylate (e.g., benzyl (meth)acrylate); ethylene, propylene, Examples include olefin monomers such as isoprene, butadiene, and isobutylene; chlorine atom-containing monomers such as vinyl chloride and vinylidene chloride; isocyanate group-containing monomers such as 2-(meth)acryloyloxyethyl isocyanate; alkoxy group-containing monomers such as methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, and ethyl carbitol (meth)acrylate; vinyl ether monomers such as methyl vinyl ether and ethyl vinyl ether; and polyfunctional monomers having two or more (e.g., three or more) polymerizable functional groups (e.g., (meth)acryloyl groups) in one molecule, such as 1,6-hexanediol di(meth)acrylate and trimethylolpropane tri(meth)acrylate.
[0029] The monomer components constituting the above acrylic polymer are monomers (m) whose homopolymer Tg is 90°C or higher. T ) and monomers (m) whose homopolymer Tg is -30°C or lower. L ) includes the above monomer (m T ) contains at least acrylonitrile (homopolymer Tg: 97°C). Therefore, the above acrylic polymer contains monomer (m L ) and monomers containing at least acrylonitrile (m T) is a polymer of monomer components, which may further contain other monomers. The Tg of each monomer homopolymer shall be the same as the glass transition temperature of the homopolymer used to calculate the calculated Tg described later, and the value described in the publicly available documents shall be used. If the Tg of the homopolymer is not described in the publicly available documents, the value obtained by the measurement method described in Japanese Patent Application Publication No. 2007-51271 shall be used.
[0030] Monomer (m T ) can increase the calculated Tg of acrylic polymers and may be useful in improving the cohesive force and high-temperature properties (e.g., suppression of the decrease in storage modulus at high temperatures, peelability at high temperatures, etc.) of coating protective materials. Monomer (m T As the monomer, acrylonitrile may be used alone, or acrylonitrile may be used in combination with other monomers whose homopolymer Tg is 90°C or higher. Other monomers whose homopolymer Tg is 90°C or higher can be appropriately selected from the various monomers mentioned above, but are not limited to these. The above other monomers can be used alone or in combination of two or more, together with acrylonitrile. Monomer (m T The upper limit of the Tg of the homopolymer of each monomer used as is not particularly limited and may be, for example, 250°C or less, 200°C or less, or 150°C or less.
[0031] Monomer (m T Non-limiting specific examples of monomers other than acrylonitrile that can be used as ) include acrylic acid, methacrylic acid, methyl methacrylate, methacrylonitrile, acryloylmorpholine, acrylamide, isobornyl acrylate, isobornyl methacrylate, dicyclopentanyl acrylate, dicyclopentanyl methacrylate, adamantyl acrylate, tert-butyl methacrylate, etc. Preferred examples include acrylic acid and methyl methacrylate.
[0032] Monomer (m TThe acrylonitrile content in ) may be, for example, 35 mol% or more, and from the viewpoint of easily achieving suitable film properties, it is appropriate to be 50 mol% or more, and preferably 60 mol% or more. In some embodiments, monomer (m T The acrylonitrile content in ) may be greater than 70 mol%, greater than 80 mol%, greater than 90 mol%, greater than 93 mol%, or 100 mol%. In some embodiments, the monomer (m T The acrylonitrile content in ) may be 85 mol% or less, 75 mol% or less, 70 mol% or less, or 65 mol% or less.
[0033] The acrylonitrile content in the total monomer components constituting the acrylic polymer may be, for example, 20 mol% or more, and from the viewpoint of easily achieving suitable film properties, it is appropriate to be 25 mol% or more (for example, 28 mol% or more), preferably 30 mol% or more, and may also be 35 mol% or more, or 40 mol% or more. The technology disclosed herein can preferably be implemented in a form in which the acrylonitrile content in the total monomer components constituting the acrylic polymer is greater than 50 mol%. Furthermore, from the viewpoint of the flexibility of the coating protective coating material, the acrylonitrile content is appropriate to be 60 mol% or less, and preferably less than 60 mol%. In some embodiments, the acrylonitrile content may be 57 mol% or less, or 56 mol% or less. The technology disclosed herein can also be implemented in a form in which the acrylonitrile content is 53 mol% or less, 50 mol% or less, and even 40 mol% or less.
[0034] Monomer (m L ) can help lower the calculated Tg of acrylic polymers and improve the low-temperature properties of coating protective coating materials (e.g., suppression of crack formation at low temperatures, suppression of cracking or tearing when peeling from the coating at low temperatures, etc.). Monomer (m LAs the monomer, one can be used if the Tg of the homopolymer is -30°C or lower, and can be selected from, for example, the various monomers mentioned above, but is not limited to these. L Monomers (m) can be used individually or in combination of two or more. L Non-limiting specific examples of monomers that can be used as ) include n-butyl acrylate (BA), 2-ethylhexyl acrylate (2EHA), isooctyl acrylate, isononyl acrylate, isoamyl acrylate, 4-hydroxybutyl acrylate (4HBA), methoxyethyl acrylate, ethyl carbitol acrylate, ethoxy-diethylene glycol acrylate, and the like.
[0035] Monomer (m L The lower limit of the Tg of the homopolymer of each monomer used as is not particularly limited and may be, for example, -100°C or higher, -90°C or higher, or -80°C or higher. In some embodiments, monomers whose homopolymer Tg is in the range of -60°C or higher and -40°C or lower are used as monomers (m L ) can be preferably adopted as monomer (m L Of these, the proportion of monomers whose homopolymer Tg is in the range of -60°C to -40°C may be, for example, 50 mol% or more, 75 mol% or more, 85 mol% or more, 95 mol% or more, or 100 mol%.
[0036] The above monomer component (m T ) and the above monomer (m L ) molar ratio (m T / m L The ratio (m) is preferably between 0.8 and 1.5. Acrylic polymers composed of monomer components of such a composition are likely to yield protective coating materials that satisfy the above-mentioned G'(23) and G'(70). In some embodiments, the above ratio (m) T / m LThe ratio (m) is preferably less than 1.5, more preferably 1.4 or less, may be 1.35 or less, may be 1.30 or less, or may be 1.25 or less. In some embodiments, the above ratio (m) T / m L The ratio (m) is preferably 1.0 or greater, and more preferably greater than 1.0. This makes it possible to realize a coating material that achieves a high level of balance between good peelability from the coating and good peelability. T / m L ) may be 1.1 or higher, 1.15 or higher, or 1.20 or higher.
[0037] The monomer components that make up acrylic polymers are monomers (m T ) and monomers (m L Other monomers, i.e., homopolymers whose glass transition temperature is higher than -30°C and lower than 90°C (hereinafter referred to as monomers (m I ) may further contain monomers (m I For example, monomers can be selected from the various monomers mentioned above, provided that the glass transition temperature of the homopolymer falls within the above range. I Monomers (m) can be used individually or in combination of two or more. I Non-limiting specific examples of monomers that can be used as ) include ethyl acrylate (EA), ethyl methacrylate, methyl acrylate (MA), n-butyl methacrylate, isobutyl methacrylate, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, cyclohexyl acrylate, cyclohexyl methacrylate, vinyl acetate, N-vinyl-2-pyrrolidone, etc.
[0038] Monomer (m I The amount used is calculated by taking the total amount of monomer components as 100 mol% and then using the monomer (m T ) and monomers (m LThe amount can be appropriately set within a range less than or equal to the amount (mol%) excluding the monomer (m I The amount used should not exceed 30 mol% of the total monomer components, preferably not exceeding 20 mol%, and more preferably not exceeding 15 mol%. The technology disclosed herein relates to monomer (m I This can preferably be carried out in which the amount of monomer (m) used is 0 mol% or more and less than 10 mol% of the total monomer components, for example, 0 mol% or more and less than 5 mol%. Here, monomer (m I The amount of monomer used is 0 mol% of the total monomer components, or at least intentionally, the monomer (m I This means not to use )
[0039] While not particularly limited, the calculated Tg of the acrylic polymer may be, for example, -50°C or higher. In some embodiments, from the viewpoint of the peelability of the protective coating material in the high-temperature range (e.g., around 70°C), it is appropriate to have a Tg of -40°C or higher, preferably -30°C or higher, and may also be -25°C or higher or -20°C or higher. Furthermore, from the viewpoint of peelability when peeling the protective coating material from the coating in low-temperature environments such as outdoors in winter (for example, suppression of peeling defects due to chipping or tearing of the protective coating material), in some embodiments, the calculated Tg of the acrylic polymer may be 10°C or lower, preferably -9°C or lower (e.g., -10°C or lower), and may also be -15°C or lower, or -20°C or lower. Having a calculated Tg of the acrylic polymer that is not too high is also advantageous from the viewpoint of suppressing the occurrence of cracks in the protective coating material due to differences in the coefficient of linear expansion between the protected object and the protected object when the protected object to which the protective coating material is applied is exposed to temperature changes.
[0040] Here, the calculated Tg of an acrylic polymer refers to the Tg determined by Fox's equation based on the composition of the monomer components used in the synthesis of the polymer. Fox's equation is a relationship between the Tg of a copolymer and the glass transition temperature Tgi of a homopolymer obtained by homopolymerizing each of the monomers constituting the copolymer, as shown below. 1 / Tg = Σ(Wi / Tgi) In Fox's equation above, Tg represents the glass transition temperature of the copolymer (unit: K), Wi represents the weight fraction of monomer i in the copolymer (weight-based copolymerization ratio), and Tgi represents the glass transition temperature of the monomer i homopolymer (unit: K).
[0041] The glass transition temperatures of homopolymers used in calculating Tg shall be those specified in publicly available documents. For example, for the monomers listed below, the following values shall be used as the glass transition temperatures of the homopolymers of those monomers. n-butyl acrylate -55℃ Acrylonitrile 97℃ Vinyl acetate 32℃ Methyl methacrylate 105℃ Acrylic acid 106℃ For the glass transition temperatures of monomer homopolymers other than those exemplified above, the values listed in the "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989) shall be used. If the Tg of a homopolymer is not listed in the publicly available documents, the value obtained by the measurement method described in Japanese Patent Publication No. 2007-51271 shall be used. Specifically, 100 parts by weight of monomer, 0.2 parts by weight of azobisisobutyronitrile, and 200 parts by weight of ethyl acetate as the polymerization solvent are added to a reactor equipped with a thermometer, stirrer, nitrogen inlet tube, and reflux condenser, and the mixture is stirred for 1 hour while circulating nitrogen gas. After removing oxygen from the polymerization system in this way, the temperature is raised to 63°C and the reaction is carried out for 10 hours. Next, the mixture is cooled to room temperature to obtain a homopolymer solution with a non-volatile content of 33% by weight. Next, this homopolymer solution is cast onto a release liner and dried to produce a test sample (sheet-like homopolymer) with a thickness of approximately 2 mm. This test sample is punched out into a 7.9 mm diameter disc shape, sandwiched between parallel plates, and measured using a viscoelasticity tester (manufactured by T.A. Instruments Japan, model name "ARES") in shear mode while applying a shear strain of 1 Hz at a frequency, in the temperature range of -70 to 150°C, with a heating rate of 5°C / min. The peak top temperature of tanδ is defined as the Tg of the homopolymer.
[0042] In some embodiments, the SP value of the acrylic polymer is greater than 9.5 (unit: cal / cm²). 3 ) 1 / 2 ]. The same applies hereafter.) is appropriate, preferably 10.0 or higher, and more preferably 10.5 or higher. Hereinafter, the SP value refers to the value of the Solubility Parameter calculated from the basic structure of the compound using the method proposed by Fedors. The SP value of such an acrylic polymer may be far from (typically farther than) the SP value of the coating film to be protected. The coating film may be, for example, a urethane coating film formed by the reaction of an acrylic polyol resin and a polyisocyanate resin. By moving the SP value of the acrylic polymer away from the SP value of the coating film, the interaction between the coating film protective coating material containing the acrylic polymer and the coating film tends to decrease. This is advantageous in terms of suppressing the occurrence of deformation of the coating film caused by the coating film protective coating material, suppressing the occurrence of peeling defects due to excessive adhesion of the coating film protective coating material to the coating film, and suppressing an increase in the burden of peeling work. In some embodiments, the SP value of the acrylic polymer may be 10.8 or higher, 11.2 or higher, or 11.5 or higher. There is no particular upper limit to the SP value of acrylic polymers; for example, it is appropriate for it to be 14.0 or less, but it may also be 13.5 or less, 13.0 or less, less than 12.5, or less than 12.0.
[0043] (Synthesis of acrylic polymers) The method for obtaining an acrylic polymer from the monomer components described above is not particularly limited. For example, known polymerization methods such as emulsion polymerization, solution polymerization, bulk polymerization, and suspension polymerization can be appropriately employed. Alternatively, active energy ray irradiation polymerization, such as photopolymerization (typically carried out in the presence of a photopolymerization initiator) using UV light, or radiation polymerization (carried out using beta rays, gamma rays, etc.), may be employed. In some preferred embodiments, the acrylic polymer is obtained by emulsion polymerization of monomer components having the above-described composition. As for the monomer supply method in the emulsion polymerization method, a batch supply method in which all monomer raw materials are supplied at once, a continuous supply (dropping) method, a divided supply (dropping) method, etc., can be appropriately employed. Some or all of the monomer components may be pre-mixed with water and an emulsifier to emulsify them, and the emulsion may be supplied to the polymerization vessel.
[0044] The polymerization temperature can be appropriately selected depending on the type of monomer and solvent used, the type of polymerization initiator, etc. A polymerization temperature of approximately 20°C or higher is appropriate, preferably approximately 40°C or higher, more preferably approximately 50°C or higher, and may also be approximately 60°C or higher, approximately 65°C or higher, and even more preferably approximately 70°C or higher. Furthermore, a polymerization temperature of approximately 170°C or lower (typically approximately 140°C or lower) is appropriate, and preferably approximately 95°C or lower (for example, approximately 85°C or lower). In emulsion polymerization, it is preferable to set the polymerization temperature to approximately 95°C or lower (for example, approximately 85°C or lower).
[0045] The solvent used for solution polymerization (polymerization solvent) can be appropriately selected from conventionally known organic solvents. For example, aromatic compounds such as toluene (typically aromatic hydrocarbons), acetic acid esters such as ethyl acetate, and aliphatic or alicyclic hydrocarbons such as hexane and cyclohexane are preferably used.
[0046] During polymerization, known or conventional thermal polymerization initiators or photopolymerization initiators may be used depending on the polymerization method and polymerization mode. Polymerization initiators can be used individually or in appropriate combinations of two or more types.
[0047] While not particularly limited, thermal polymerization initiators can be used, for example, azo polymerization initiators, peroxide initiators, redox initiators consisting of a combination of peroxide and reducing agent, substituted ethane initiators, etc. Examples of azo initiators include 2,2'-azobisisobutyronitrile, 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine]hydrate, 2,2'-azobis(2-methylpropionamidine) disulfate, 2,2'-azobis(2-methylpropionamidine) dihydrochloride, 2,2'-azobis(2-methylpropionamidine) dihydrochloride, 2,2'-azobis[2-(5-methyl-2-imidazolin-2-yl)propane] dihydrochloride, and 2,2'-azobis(N,N'-dimethyleneisobutylamidine) dihydrochloride. Examples of peroxide initiators include persulfates such as potassium persulfate and ammonium persulfate; benzoyl peroxide, t-butyl hydroperoxide, di-t-butyl peroxide, dicumyl peroxide, dilauroyl peroxide, di-n-octanoyl peroxide, di(4-methylbenzoyl) peroxide, t-butyl peroxybenzoate, t-butyl peroxyisobutyrate, t-hexyl peroxypivalate, t-butyl peroxypivalate, di(2-ethylhexyl Examples include sil)peroxydicarbonate, di(4-t-butylcyclohexyl)peroxydicarbonate, di-sec-butylperoxydicarbonate, t-butylperoxyneodecanoate, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)cyclododecane, 1,1-bis(t-hexylperoxy)cyclohexane, hydrogen peroxide, etc. Examples of redox initiators include combinations of peroxides and ascorbic acid (such as hydrogen peroxide and ascorbic acid), combinations of peroxides and iron(II) salts (such as hydrogen peroxide and iron(II) salts), and combinations of persulfates and sodium bisulfite.
[0048] While not particularly limited, the following can be used as photopolymerization initiators: ketal-based photopolymerization initiators, acetophenone-based photopolymerization initiators, benzoin ether-based photopolymerization initiators, acylphosphine oxide-based photopolymerization initiators, α-ketol-based photopolymerization initiators, aromatic sulfonyl chloride-based photopolymerization initiators, photoactive oxime-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzyl-based photopolymerization initiators, benzophenone-based photopolymerization initiators, thioxanthone-based photopolymerization initiators, and the like.
[0049] The amount of polymerization initiator used can be the usual amount depending on the polymerization method and polymerization mode, and is not particularly limited. For example, approximately 0.001 to 5 parts by weight (typically approximately 0.01 to 2 parts by weight, for example, approximately 0.01 to 1 part by weight) of polymerization initiator can be used per 100 parts by weight of the monomer to be polymerized.
[0050] During polymerization, various conventionally known chain transfer agents (which may also be understood as molecular weight modifiers or degree of polymerization modifiers) can be used as needed. Chain transfer agents can be used individually or in combination of two or more. Mercaptans such as n-dodecyl mercaptan, t-dodecyl mercaptan, and thioglycolic acid can be used as chain transfer agents. Alternatively, chain transfer agents that do not contain sulfur atoms (non-sulfur chain transfer agents) may be used. Specific examples of non-sulfur chain transfer agents include anilines such as N,N-dimethylaniline and N,N-diethylaniline; terpenoids such as α-pinene and terpinolene; styrenes such as α-methylstyrene and α-methylstyrene dimer; compounds having a benzylidenyl group such as dibenzylideneacetone, cinnamyl alcohol, and cinnamyl aldehyde; hydroquinones such as hydroquinone and naphthohydroquinone; quinones such as benzoquinone and naphthoquinone; olefins such as 2,3-dimethyl-2-butene and 1,5-cyclooctadiene; alcohols such as phenol, benzyl alcohol, and allyl alcohol; and benzyl hydrogens such as diphenylbenzene and triphenylbenzene. When a chain transfer agent is used, the amount used can be approximately 0.01 to 1 part by weight per 100 parts by weight of the monomer component. The technology disclosed herein can also be preferably implemented in a form that does not use a chain transfer agent.
[0051] Emulsification polymerization is usually carried out in the presence of an emulsifier. The emulsifier used for emulsion polymerization is not particularly limited, and known anionic emulsifiers, nonionic emulsifiers, etc., can be used. The emulsifier can be used alone or in combination of two or more.
[0052] Non-limiting examples of anionic emulsifiers include sodium lauryl sulfate, ammonium lauryl sulfate, sodium dodecylbenzenesulfonate, sodium polyoxyethylene lauryl sulfate, sodium polyoxyethylene alkyl ether sulfate, ammonium polyoxyethylene alkylphenyl ether sulfate, sodium polyoxyethylene alkylphenyl ether sulfate, and sodium polyoxyethylene alkyl sulfosuccinate. Non-limiting examples of nonionic emulsifiers include polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene fatty acid esters, and polyoxyethylene polyoxypropylene block polymers. Emulsifiers having reactive functional groups (reactive emulsifiers) may also be used. Examples of reactive emulsifiers include radical polymerizable emulsifiers, which have a structure in which radical polymerizable functional groups such as propenyl groups and allyl ether groups are introduced into the above-mentioned anionic or nonionic emulsifiers.
[0053] The amount of emulsifier used in emulsion polymerization may be, for example, 0.2 parts by weight or more, 0.5 parts by weight or more, 1.0 part by weight or more, or 1.5 parts by weight or more, per 100 parts by weight of monomer component. In some embodiments, the amount of emulsifier used is usually appropriate to be 10 parts by weight or less, preferably 5 parts by weight or less, and may be 3 parts by weight or less, per 100 parts by weight of monomer component.
[0054] Emulsion polymerization may be carried out in the presence of a protective colloid. Examples of protective colloids include polyvinyl alcohols such as partially saponified polyvinyl alcohol, fully saponified polyvinyl alcohol, and modified polyvinyl alcohol; cellulose derivatives such as hydroxyethylcellulose, hydroxypropylcellulose, and carboxymethylcellulose salts; and natural polysaccharides such as guar gum. The degree of saponification of partially saponified polyvinyl alcohol is typically less than 95 mol%, but may also be less than 92 mol% or less than 90 mol%. There is no particular lower limit to the degree of saponification of partially saponified polyvinyl alcohol, but from the viewpoint of emulsion stability, it is appropriate to be 65 mol% or more, preferably 70 mol% or more, and more preferably 80 mol% or more (e.g., 85 mol% or more). Examples of the above-mentioned modified polyvinyl alcohols include anionic modified polyvinyl alcohol into which anionic groups such as carboxyl groups and sulfonic acid groups have been introduced; and cationic modified polyvinyl alcohol into which cationic groups such as quaternary ammonium salts have been introduced. The degree of saponification of the modified polyvinyl alcohol may be, for example, less than 98 mol%, but may also be less than 95 mol%, less than 92 mol%, or less than 90 mol%. Furthermore, the lower limit of the degree of saponification of the modified polyvinyl alcohol may be, for example, 55 mol% or more, and from the viewpoint of emulsion stability, 65 mol% or more is appropriate, 70 mol% or more is preferred, and 80 mol% or more (for example, 85 mol% or more) is more preferred. The protective colloid can be used alone or in combination of two or more types.
[0055] The amount of protective colloid used is appropriately 0.1 parts by weight or more per 100 parts by weight of monomer component, preferably 0.5 parts by weight or more (e.g., 0.7 parts by weight or more), and preferably 10 parts by weight or less, and preferably 5 parts by weight or less (e.g., 3 parts by weight or less, or 2 parts by weight or less). The protective colloid is preferably used in combination with the emulsifier as described above, but is not limited thereto, and the protective colloid may be used without an emulsifier. For example, emulsion polymerization can be carried out by placing water and protective colloid in a polymerization container, and supplying an emulsified solution, which is obtained by pre-mixing some or all of the monomer component with water and an emulsifier, to the polymerization container. When using an anionic protective colloid (e.g., anionic modified polyvinyl alcohol) in combination with an emulsifier, from the viewpoint of polymerization stability, it is preferable to use one or more types selected from the group consisting of anionic emulsifiers and nonionic emulsifiers as the emulsifier.
[0056] In some preferred embodiments, emulsion polymerization is carried out in the presence of anionically modified polyvinyl alcohol. The aqueous emulsion of the acrylic polymer obtained by such emulsion polymerization tends to exhibit a readily viscous effect when a thickening agent is added. By using such an aqueous emulsion of the acrylic polymer, an acrylic coating composition exhibiting good viscosity characteristics suitable for slot die coating can be suitably prepared. Preferred examples of anionically modified polyvinyl alcohol include sulfonic acid group-modified polyvinyl alcohol and carboxylated polyvinyl alcohol. For example, sulfonic acid group-modified polyvinyl alcohol and / or carboxylated polyvinyl alcohol can be preferably used. Anionically modified polyvinyl alcohol may also be used in combination with an emulsifier.
[0057] <Acrylic coating composition> The acrylic coating compositions disclosed herein include any of the above-mentioned acrylic polymers as a base polymer. The form of the acrylic coating composition is not particularly limited and may include, for example, an aqueous emulsion type composition in which the acrylic polymer is dispersed in an aqueous solvent, or a solvent type composition in which the acrylic polymer is dissolved in an organic solvent. From the viewpoint of environmental hygiene, an aqueous emulsion type coating composition is preferred. The following description will mainly focus on aqueous emulsion type coating compositions, but the acrylic coating compositions disclosed herein are not intended to be limited to aqueous emulsion type compositions.
[0058] In an aqueous emulsion-type coating composition, the aqueous solvent refers to water or a mixed solvent having water as the main component (a component present in more than 50% by weight). The solvents other than water constituting this mixed solvent may be one or more selected from various organic solvents (such as lower alcohols) that can be uniformly mixed with water. The aqueous solvent in this specification typically has a water content of 90% by weight or more, preferably 95-100% by weight.
[0059] The coating compositions disclosed herein may optionally contain various additives. Examples of such additives include known thickeners, thixotropes, dispersants, defoamers, and inorganic powders. For example, an aqueous emulsion type coating composition can be prepared by blending various additives with an aqueous emulsion (polymerization reaction solution) of an acrylic polymer obtained by the emulsion polymerization described above. Alternatively, the aqueous emulsion of the acrylic polymer may be used as is, or the aqueous emulsion may be pH-adjusted (for example, by adding aqueous ammonia to adjust the pH to about 6-8) and / or its concentration adjusted (for example, by adding water to adjust the solid content to about 40-60% by weight) before being used as the coating composition.
[0060] By incorporating inorganic powder into a coating composition, a coating material containing inorganic powder is formed. With such a coating material, the inorganic powder can block light such as ultraviolet rays, thereby suppressing photodegradation of the coating material itself and the coating film protected by the coating material. Suitable inorganic powders include oxides such as titanium dioxide, zinc oxide, magnesium oxide, alumina, and silica; carbonates such as calcium carbonate; sulfates such as barium sulfate; and the like. Inorganic powders that can color the coating protective coating material white are preferred. With a white coating protective coating material, for example, the deterioration of the coating material and the coating film can be better suppressed by suppressing the temperature rise caused by sunlight irradiation.
[0061] The amount of inorganic powder used per 100 parts by weight of acrylic polymer can be, for example, 0.5 parts by weight or more, and from the viewpoint of light shielding effect, it is appropriate to use 1 part by weight or more, preferably 2 parts by weight or more, more preferably 3 parts by weight or more, and may also be 5 parts by weight or more, 10 parts by weight or more, 15 parts by weight or more, or 20 parts by weight or more. Furthermore, the amount of inorganic powder used per 100 parts by weight of acrylic polymer can be, for example, 100 parts by weight or less, and from the viewpoint of coating material strength and film formation properties, it is appropriate to use 80 parts by weight or less, advantageous to use 60 parts by weight or less, preferably 50 parts by weight or less, and may also be 40 parts by weight or less, or 30 parts by weight or less.
[0062] In several preferred embodiments, the inorganic powder contains at least titanium dioxide (TiO2). Titanium dioxide may be used in combination with one or more other inorganic powders (e.g., calcium carbonate). The type of titanium dioxide is not particularly limited, and any crystalline form of titanium dioxide, such as rutile, anatase, or brookite, can be used. Rutile titanium dioxide is preferred. Titanium dioxide with a coating applied to the particle surface may also be used. The material used to coat the titanium dioxide particles is not particularly limited and can be an inorganic oxide such as silica, alumina, or zinc oxide. A preferred example is a highly weather-resistant type of titanium dioxide (typically rutile titanium dioxide) with the particle surface coated with Si-Al2O3 or the like.
[0063] The amount of titanium dioxide used per 100 parts by weight of acrylic polymer can be, for example, 0.1 parts by weight or more, and from the viewpoint of light shielding effect, it is appropriate to use 0.5 parts by weight or more, preferably 1 part by weight or more, more preferably 2 parts by weight or more, and may also be 3 parts by weight or more. Furthermore, the amount of titanium dioxide used per 100 parts by weight of acrylic polymer can be, for example, 30 parts by weight or less, appropriate to use 20 parts by weight or less, preferably 15 parts by weight or less, may also be 10 parts by weight or less, and may also be 8 parts by weight or less.
[0064] The average particle size of the inorganic powder is not particularly limited. For example, from the viewpoint of obtaining a good light shielding effect, the average particle size of the inorganic powder is preferably 150 nm or more, more preferably 180 nm or more, and may also be 220 nm or more, or 250 nm or more. On the other hand, from the viewpoint of dispersibility in the resin component, the average particle size of the inorganic powder is suitable to be 2000 nm or less, preferably 1500 nm or less, more preferably 1000 nm or less (e.g., 800 nm or less), and may also be 500 nm or less, 400 nm or less, or 350 nm or less. For example, titanium oxide particles with an average particle size of about 250 to 350 nm can be preferably used.
[0065] Thickening agents can be used to adjust the viscosity properties of the coating composition. Known thickening agents such as urethane-based thickening agents, cellulose-based thickening agents, polyether-based thickening agents, and acrylic-based thickening agents can be used. Thickening agents can be used individually or in appropriate combinations of two or more. Examples of commercially available urethane-based thickeners include BYK's product names "RHEOBYK-H 3300VF," "RHEOBYK-T 1010," and "RHEOBYK-L 1400," ADEKA's product names "Adekanol UH-450VF," "Adekanol UH-420," "Adekanol UH-462," "Adekanol UH-472," "Adekanol UH-540," "Adekanol UH-756VF," and "Adekanol UH-814N," and Sunnopco's product names "SN Thickener 612," "SN Thickener 621N," "SN Thickener 625N," "SN Thickener 627N," and "SN Thickener 660T." In some embodiments, urethane association type thickeners can be preferably used as urethane-based thickeners. Suitable examples of urethane-associated thickeners include BYK's product names "RHEOBYK-H 3300VF," "RHEOBYK-T 1010," and "RHEOBYK-L 1400," and ADEKA's product names "ADEKA UH-450VF" and "ADEKA UH-420."
[0066] Examples of cellulose-based thickeners include hydroxyethylcellulose, carboxymethylcellulose, and methylcellulose. A commercially available example is "SANHEC L" manufactured by Sansho Co., Ltd. Examples of polyether-based thickeners include polyethylene glycol, polyether dialkyl esters, polyether dialkyl ethers, and polyether epoxy modified products. A commercially available example is "POLYOX WSR N-80" manufactured by Dow Chemical. Examples of acrylic thickeners include acrylic acid polymers such as sodium polyacrylate. Commercially available products include, for example, "Primal ASE-60," "Primal TT-615," and "Primal RM-5" from Rohm & Haas, and "SN Thickener 613," "SN Thickener 618," "SN Thickener 630," "SN Thickener 634," and "SN Thickener 636" from Sunnopco.
[0067] The amount of thickener used is not particularly limited and can be adjusted as appropriate to obtain the desired viscosity characteristics. From the viewpoint of suppressing excessive influence on film properties, in some embodiments, the amount of thickener used per 100 parts by weight of acrylic polymer is appropriate to be 15 parts by weight or less, preferably 10 parts by weight or less, more preferably 5 parts by weight or less (e.g., 3 parts by weight or less), and may also be 2.5 parts by weight or less, or 2 parts by weight or less. The lower limit of the amount of thickener used is not particularly limited and may be 0.01 parts by weight or more, 0.05 parts by weight or more, or 0.1 parts by weight or more per 100 parts by weight of acrylic polymer.
[0068] Thixotropes can be useful for adjusting the viscosity properties of coating compositions. Inorganic materials such as bentonite, modified bentonite, montmorillonite, and hectorite can be used as thixotropes. Thixotropes can be used individually or in combination of two or more. The amount of thixotropin used is not particularly limited and can be adjusted as appropriate to obtain the desired viscosity characteristics. From the viewpoint of suppressing excessive influence on film properties, in some embodiments, the amount of thixotropin used per 100 parts by weight of acrylic polymer is appropriate to be 10 parts by weight or less, preferably 5 parts by weight or less, and may also be 3 parts by weight or less, 2.5 parts by weight or less, or 2 parts by weight or less. The lower limit of the amount of thixotropin used is not particularly limited and may be 0.01 parts by weight or more, 0.05 parts by weight or more, or 0.1 parts by weight or more per 100 parts by weight of acrylic polymer.
[0069] The thixotropic agent may also function as a thickening agent. The thickening agents and thixotropic agents described above may be used in combination, or either one may be used alone. When the thickening agents and thixotropic agents are used in combination, the total amount used may be, for example, 15 parts by weight or less, 10 parts by weight or less, 5 parts by weight or less, 4 parts by weight or less, or 2.5 parts by weight or less per 100 parts by weight of the acrylic polymer, or 0.01 parts by weight or more, 0.05 parts by weight or more, or 0.1 parts by weight or more.
[0070] Methods for applying the coating composition onto the coating film of an object to be protected include, for example, application by a coater such as a die coater or spray coater, roller application, dip coating, etc. The application by a die coater may be performed by a coating system including a robotic arm equipped with a slit die. For example, by controlling the robotic arm so that the slit die moves along the shape of the object to be protected while discharging the coating composition in a continuous liquid film (ribbon shape), the coating composition can be applied to the object to be protected efficiently and accurately, even if the object to be protected has a non-planar shape (for example, a complex three-dimensional shape such as the exterior panel of an automobile).
[0071] Drying the applied coating composition is preferably carried out under heating, from the viewpoint of improving the efficiency and precision of coating material formation. The drying temperature can be, for example, around 40°C to 100°C, and is usually preferably around 60°C to 90°C.
[0072] While not particularly limited, from the viewpoint of ease of coating and film thickness control, the solid content of the coating composition is suitable at approximately 25 to 75% by weight, and preferably at approximately 30 to 70% by weight. The solid content can be adjusted by the amount of solvent (e.g., aqueous solvent) used. For example, the solid content of the coating composition can be adjusted by adjusting the amount of water used in emulsion polymerization or by adding water after the emulsion polymerization is completed.
[0073] The thickness of the protective coating material is not particularly limited, but from the viewpoint of enhancing the protective effect, it is appropriate to have a thickness of 20 μm or more, and from the viewpoint of strength and peelability, it is preferable to have a thickness of 50 μm or more, and more preferably 70 μm or more (for example, 85 μm or more). The thickness of the coating material can be adjusted by the amount of coating composition applied and the solid content. From the viewpoint of drying properties and preventing sagging of the applied composition, the thickness of the protective coating material is appropriate to have a thickness of 300 μm or less, preferably 200 μm or less, and more preferably 150 μm or less.
[0074] (BH viscosity) In some embodiments, the viscosity V1 of the coating composition, as measured by a BH-type viscometer at 2 rpm, is appropriately 20 Pa·s or higher, preferably 40 Pa·s or higher, and more preferably 55 Pa·s or higher. As the viscosity V1 measured under such low shear rate conditions increases, the anti-sagging properties of the coating composition applied to the object to be protected tend to improve. On the other hand, from the viewpoint of the defoaming and leveling properties of the coating composition, the viscosity V1 of the coating composition is appropriately 200 Pa·s or less, preferably 150 Pa·s or less, and more preferably 100 Pa·s or less (e.g., 80 Pa·s or less).
[0075] The viscosity V3 of the above coating composition, as measured by a BH-type viscometer at 20 rpm, is not particularly limited and may be, for example, around 5 Pa·s to 50 Pa·s. When viscosity V3 is within this range, the viscosity V1 described above is easily obtained. The viscosity of the coating composition as measured by a BH-type viscometer (BH viscosity) is measured by the method described in the examples below.
[0076] (Rheometer viscosity) In some embodiments, the above coating composition has a shear rate of 100 sec measured by a cone-plate rheometer. -1 The viscosity V2 is preferably 1.0 Pa·s or higher, more preferably 1.3 Pa·s or higher, and may also be 1.5 Pa·s or higher, 2.0 Pa·s or higher, or 2.3 Pa·s or higher. By setting the viscosity V2 measured under such high shear rate conditions to a predetermined level or higher, the coating properties (die coating properties) by slot dies can be improved. There is no particular upper limit to the viscosity V2, but from the viewpoint of ease of compatibility with defoaming properties and ease of liquid transfer, it is appropriate to be 15 Pa·s or less, preferably 10 Pa·s or less, may also be 8.5 Pa·s or less, or 6.0 Pa·s or less. The viscosity of the coating composition measured by the rheometer (rheometer viscosity) is measured by the method described in the examples below.
[0077] <Coating material for protecting paint film> The coating protective coating material disclosed herein can be formed using the coating composition described above. For example, the coating composition is applied (preferably by a slot die) onto the coating of an object to be protected and dried. This makes it possible to provide a coating protective coating material 10 formed from the coating composition on the coating 22 of an object to be protected 20 having a coating 22, for example, as shown in Figure 1.
[0078] The above-mentioned protective coating material preferably has a storage modulus (G'(23)) of 150 MPa or higher at 23°C, more preferably 180 MPa or higher, and may also be 230 MPa or higher, or 250 MPa or higher. Coating materials with a G'(23) above the specified level tend not to tear or stretch excessively when peeled off from the coating at room temperature. This is advantageous from the viewpoint of improving peelability. In some embodiments, a G'(23) of approximately 1000 MPa or less is appropriate. Having a G'(23) that is not too high is advantageous from the viewpoint of suppressing marks on the coating. It is also advantageous from the viewpoint of peelability because it is easier to initiate peeling when removing the coating material from the coating (for example, by scratching the edge of the coating material with a fingernail or the like to lift it away from the coating). In some embodiments, G'(23) may be 800 MPa or less, 700 MPa or less, 600 MPa or less, 500 MPa or less, or 400 MPa or less.
[0079] The above-mentioned protective coating material is preferably of a storage modulus (G'(70)) of 0.40 MPa or higher at 70°C, and preferably of 0.45 MPa or higher. A coating material with a G'(70) of a predetermined value or higher will not become excessively soft even at temperatures higher than room temperature, such as when the protected object to which the coating material is applied is placed outdoors in the summer, and will be able to be properly peeled off the coating film. From the viewpoint of improving peelability at high temperatures, in some embodiments, it is advantageous for G'(70) to be 0.5 MPa or higher, preferably 0.70 MPa or higher, and may also be 1.0 MPa or higher, or 1.2 MPa or higher. Furthermore, there is no particular upper limit to G'(70), but from the viewpoint of making it easier to achieve the above-mentioned 23°C storage modulus, it is appropriate for it to be 5 MPa or lower, preferably 3 MPa or lower, and may also be 2.5 MPa or lower, or 2.0 MPa or lower. In some embodiments, G'(70) may be 1.5 MPa or lower, or 1.2 MPa or lower. Having a G'(70) that is not too high is also advantageous from the standpoint of suppressing marks on the paint film.
[0080] The storage modulus of the protective coating material at 23°C, 70°C, or other temperatures is measured by the method described in the examples below.
[0081] In some embodiments of the protective coating materials disclosed herein, the coating material is preferably, more preferably, 30°C or higher, and more preferably 34°C or higher, having a glass transition temperature (hereinafter also referred to as "RSA-Tg") determined as the peak top temperature of tanδ in viscoelasticity measurements. Furthermore, the RSA-Tg may be, for example, 50°C or lower, 45°C or lower, or 43°C or lower (for example, 41°C or lower). Protective coating materials with an RSA-Tg within the above range are likely to satisfy the above-mentioned G'(23) and G'(70). In some embodiments of the coating material, it is appropriate that the glass transition temperature (hereinafter also referred to as "RSA-Tg(G)"), which is determined as the temperature corresponding to the inflection point of the loss modulus G'' in viscoelasticity measurement, is 5°C or higher, preferably 15°C or higher, and more preferably 20°C or higher. Furthermore, RSA-Tg(G) may be, for example, 40°C or lower, 35°C or lower, or 30°C or lower (for example, 25°C or lower). With a coating protective material in which RSA-Tg(G)'' is within the above range, it is easy to obtain a coating protective material that satisfies the above-mentioned G'(23) and G'(70). Furthermore, the RSA-Tg(G) values for Examples A1 to A10 in the examples described below were as follows: A1: 20.2°C, A2: 21.2°C, A3: 21.8°C, A4: 22.3°C, A5: 24.5°C, A6: 22.2°C, A7: 5.5°C, A8: 17.5°C, A9: 34.8°C, A10: 37.2°C.
[0082] The protective coating material disclosed herein is suitable to have a breaking strength of 20 N / 25 mm or more, as measured by the tensile test described in the examples below, and preferably 30 N / 25 mm or more. The protective coating material disclosed herein is suitable to have a yield strength of 2 N / 25 mm or more and 12 N / 25 mm or less, as measured by the tensile test described in the examples below, and preferably 4 N / 25 mm or more and 10 N / 25 mm or less. The protective coating material disclosed herein is suitable to have a break elongation of 150% or more, as measured by the tensile test described in the examples below, and preferably 250% or more. The upper limit of the break elongation is suitable to be, for example, 500% or less. Such a coating material can distribute stress by deforming appropriately when peeled off from the coating film, thereby suppressing rupture of the coating material due to localized stress concentration. A protective coating material that achieves a good balance of the above-mentioned breaking strength, yield strength, and elongation at breaking (for example, all of which are 1 point or higher according to the evaluation standards described in the examples below) is preferable from the viewpoint of workability when peeling off the coating.
[0083] This specification provides a method for protecting a coating film, comprising: preparing a coating composition containing an acrylic polymer as a base polymer; applying the coating composition onto a coating film on an object to be protected; and drying the coating composition to form a coating protective coating material that temporarily protects the coating film. One embodiment of the above coating protection method will be described with reference to Figure 2. Specifically, one of the acrylic coating compositions disclosed herein is prepared (step S10). This coating composition is applied to the coating of an object to be protected (for example, by applying with a slot die) (step S20). The applied coating composition is dried to form a coating protective coating material that temporarily protects the coating (step S30). By providing a coating material on the coating in this way, the coating can be protected from damage and deterioration. The coating material, having completed its protective role, is peeled off from the coating at a desired timing (for example, by peeling) (step S40).
[0084] The matters disclosed in this specification include the following: [1] A protective coating material formed from an acrylic coating composition containing an acrylic polymer as a base polymer, The monomer components constituting the above acrylic polymer are monomers (m) whose homopolymer glass transition temperature is 90°C or higher. T ) and monomers (m) whose homopolymer glass transition temperature is -30°C or lower. L ) and, where the above monomer (m T ) contains at least acrylonitrile, The above monomer component (m T ) and the above monomer (m L ) molar ratio (m T / m L ) is between 0.8 and 1.5, A protective coating material having a storage modulus of 150 MPa or more and 1000 MPa or less at 23°C, and a storage modulus of 0.40 MPa or more at 70°C. [2] The acrylic polymer described above has a glass transition temperature of -30°C or higher and -5°C or lower, calculated based on the composition of the monomer components, as described in [1] above. [3] The coating protective material according to [1] or [2] above, wherein the acrylonitrile content in the monomer component is greater than 50 mol%. [4] A protective coating material according to any one of [1] to [3] above, further comprising 1 to 60 parts by weight of inorganic powder per 100 parts by weight of the above acrylic polymer. [5] The inorganic powder is the coating protective material described in [4] above, wherein the inorganic powder contains titanium dioxide. [6] The acrylic coating composition is an aqueous emulsion composition in which the acrylic polymer is dispersed in an aqueous solvent, as described in any of [1] to [5] above, which is a protective coating material for a coating film. [7] A protective coating material for paint films according to any one of [1] to [6] above, which contains anionic polyvinyl alcohol. [8] A protective coating material for paint films according to any of [1] to [7] above, which contains a thickening agent. [9] A protective coating material according to any of [1] to [8] above, having a thickness of 20 μm or more and 300 μm or less.
[0085]
[10] An acrylic coating composition for forming a protective coating material, It contains an acrylic polymer as the base polymer, The monomer components constituting the above acrylic polymer are monomers (m) whose homopolymer glass transition temperature is 90°C or higher. T ) and monomers (m) whose homopolymer glass transition temperature is -30°C or lower. L ) and, where the above monomer (m T ) contains at least acrylonitrile, The above monomer component (m T ) and the above monomer (m L ) molar ratio (m T / m L An acrylic coating composition in which the ratio is 0.8 or more and 1.5 or less.
[11] The acrylic coating composition described in
[10] above, which forms a protective coating material having a storage modulus of 150 MPa or more and 1000 MPa or less at 23°C, and a storage modulus of 0.40 MPa or more at 70°C.
[12] The acrylic coating composition according to
[10] or
[11] , wherein the acrylic polymer has a glass transition temperature of -30°C or higher and -5°C or lower, calculated based on the composition of the monomer components.
[13] The acrylic coating composition according to any one of
[10] to
[12] above, wherein the acrylonitrile content in the monomer component is greater than 50 mol%.
[14] The acrylic coating composition according to any one of
[10] to
[13] above, further comprising 1 to 60 parts by weight of inorganic powder per 100 parts by weight of the above acrylic polymer.
[15] The acrylic coating composition described in
[14] above, wherein the inorganic powder contains titanium dioxide.
[16] The acrylic coating composition according to any one of
[10] to
[15] above, wherein the acrylic coating composition is an aqueous emulsion composition in which the acrylic polymer is dispersed in an aqueous solvent.
[17] The acrylic coating composition according to any one of
[10] to
[16] above, wherein the acrylic polymer is emulsion polymerized in the presence of a protective colloid.
[18] The acrylic coating composition according to
[17] above, wherein the protective colloid is anionic polyvinyl alcohol.
[19] An acrylic coating composition according to any one of
[10] to
[18] above, which contains a thickening agent.
[20] The above acrylic coating composition has a viscosity V1 measured by a BH-type viscometer at 2 rpm of 20 Pa·s or more and 200 Pa·s or less, and Shear rate measured at 100 sec using a cone-plate rheometer. -1 An acrylic coating composition according to any one of the above
[10] to
[19] , wherein the viscosity V2 at is 1.0 Pa·s or more.
[0086] 〔21〕 Prepare an acrylic coating composition containing an acrylic polymer as a base polymer. Apply the acrylic coating composition onto the coating film of an object to be protected having a coating film, and Dry the acrylic coating composition to form a coating film protection coating material that temporarily protects the coating film. including The monomer components constituting the acrylic polymer include a monomer (m T ) whose glass transition temperature of the homopolymer is 90°C or higher, and a monomer (m L ) whose glass transition temperature of the homopolymer is -30°C or lower. Here, the monomer (m T ) contains at least acrylonitrile. In the monomer components, the molar ratio (m T ) of the monomer (m L ) to the monomer (m T / m L ) is 0.8 or more and 1.5 or less. A coating film protection method. 〔22〕 The coating film protection coating material is the coating film protection coating material according to any one of the above-mentioned 〔1〕 to 〔9〕. The coating film protection method according to 〔21〕 above. 〔23〕 As the acrylic coating composition, use the acrylic coating composition according to any one of the above-mentioned 〔10〕 to 〔20〕. The coating film protection method according to 〔21〕 or 〔22〕 above. 〔24〕 The application of the acrylic coating composition is performed by a slot die. The coating film protection method according to any one of 〔21〕 to 〔23〕 above. <了
Example
[0087] Hereinafter, several experimental examples related to the present invention will be described, but it is not intended to limit the present invention to those shown in such specific examples. In the following description, "parts" and "%" representing the usage amount and content are based on weight unless otherwise specified. Also, unless otherwise specified, the usage amount of each material is based on the active ingredient amount.
[0088] Experimental Example 1 <Preparation of coating composition> (Example A1) A monomer emulsion was prepared by mixing 66.4 parts (45 mol%) of n-butyl acrylate (BA), 33.6 parts (55 mol%) of acrylonitrile (AN), 0.05 parts of n-lauryl mercaptan, 2 parts of polyoxyethylene lauryl sulfate sodium (Kao Corporation, product name "Latemul E118B"), and 40 parts of ion-exchanged water, and emulsifying the mixture in an emulsifier (homomicker) while purging with nitrogen. Fifty parts of deionized water were placed in a reaction vessel equipped with a condenser, nitrogen inlet tube, thermometer, and stirrer. One part of anionically modified polyvinyl alcohol (Nippon Synthetic Chemical Industry Co., Ltd., trade name "Gosenex L-3266"; saponification degree 86.5-89.0 mol%) was added, and the mixture was dissolved at room temperature while introducing nitrogen gas. The temperature was then raised to 60°C, and 0.1 parts of 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine]hydrate (Wako Pure Chemical Industries, Ltd., trade name "VA-057") was added as a polymerization initiator. While maintaining the liquid temperature in the reaction vessel at around 60°C, the monomer emulsion was added over 3 hours to carry out the polymerization reaction. After the addition of the monomer emulsion was completed, the mixture was maintained at the same temperature for another 3 hours to mature. After cooling the system to room temperature, the pH was adjusted to 7.5 by adding 10% ammonium water to obtain an aqueous emulsion of an acrylic polymer. This aqueous emulsion was used as the acrylic coating composition in this example.
[0089] (Example A2~A10) Aqueous emulsions (acrylic coating compositions) of acrylic polymers for each example were obtained in the same manner as in Example A1, except that the type and amount of monomer used were changed as shown in Table 1.
[0090] <Measurement and Evaluation> [Tensile test] A painted steel plate, coated with an acid epoxy cross-linked acrylic paint (manufactured by Kansai Paint Co., Ltd., product name "KINO1210TW"), was held horizontally with the painted surface facing upwards. The coating composition for each example was applied to the painted surface of the painted steel plate using an applicator manufactured by TP Giken Co., Ltd., and dried at 80°C for 3 minutes to form a film (coating protective coating material). The amount of coating composition applied was set so that the thickness in terms of solid content was 100 μm. The formed film was peeled from the painted steel plate at room temperature and cut into strips 25 mm wide and 100 mm long to prepare measurement samples for tensile testing. Under conditions of 23°C and 50% RH, the above-mentioned sample was placed in a tensile testing machine (Shimadzu Corporation, machine name "Tensilon"), and a tensile test was performed at a gauge length of 50 mm and a tensile speed of 0.3 m / min to measure the breaking strength [N / 25 mm], yield strength [N / 25 mm], and elongation at break.
[0091] The results obtained were classified according to the following levels and are shown in Table 1. (Breaking strength) 3 points: 30N / 25mm or more 2 points: 20N / 25mm or more, less than 30N / 25mm 1 point: 20N / less than 25mm (yield point strength) 3 points: 4N / 25mm or more, less than 10N / 25mm Two points: 2N / 25mm or more and less than 4N / 25mm, or 10N / 25mm or more and 12N / 25mm or less. 1 point: Less than 2N / 25mm or more than 12N / 25mm (Elongation at break) 3 points: 250% or more 2 points: 150% or more but less than 250% 1 point: Less than 150%
[0092] [Peeling properties] The evaluation scores for the fracture strength, yield strength, and elongation at fracture were totaled, and based on this total score, the peelability at room temperature was evaluated at the following three levels. The results are shown in Table 1. 7 points or higher: G (Good; indicates good peeling properties) 5-6 points: A (Acceptable; indicates practically acceptable peelability) 4 points or less: P (Poor; poor peelability)
[0093] [Measurement of storage modulus] Using the coating composition for each example, a 100 μm thick film was formed on the painted steel plate in the same manner as the film preparation for the tensile test described above. The formed film was peeled from the painted steel plate at room temperature, and multiple films were stacked and integrated under pressure to produce a laminated film with a thickness of approximately 1 mm. A measurement sample was prepared by punching this laminated film into a 7.9 mm diameter disc shape. This sample was sandwiched between parallel plates, and the viscoelasticity was measured using a viscoelasticity tester (TA Instruments, name "ARES G2") in shear mode while applying a shear strain at a frequency of 1 Hz over a temperature range of -70 to 150°C at a heating rate of 5°C / min. The storage modulus G' at each temperature was determined. The results are shown in Table 1.
[0094] [RSA-Tg] The peak top temperature of tanδ was determined from the viscoelasticity measurements described above, and this temperature is shown in Table 1 as RSA-Tg.
[0095] [70°C peelability] The coating compositions according to each example were applied to the painted steel sheet using an applicator manufactured by TP Giken Co., Ltd., and a film (coating protective coating material) was formed by drying at 80°C for 3 minutes. Next, the painted steel sheet was placed in a constant temperature bath at 70°C, and the peelability of the film when peeling it off the painted steel sheet at this temperature was evaluated at the following two levels. G (Good): The film can be peeled off (good peelability at 70°C). P (Poor): The film cannot be peeled off and stretches and tears (poor release properties at 70°C).
[0096] [Table 1]
[0097] As shown in Table 1, the films formed from the coating compositions of Examples A1 to A6 all had good peelability from the coating film and were peelable from the coating film even at 70°C. On the other hand, in the films formed from the coating compositions of Examples A7 to A9 in which the molar ratio (m T / m L ) of the monomer components constituting the base polymer was less than 0.8 or greater than 1.5, or in the film formed from the coating composition of Example A10 in which the above monomer component did not contain acrylonitrile, it was not possible to achieve both good peelability and peelability at 70°C.
[0098] Experimental Example 2 <Preparation of Coating Composition> (Example B1) To the acrylic coating composition of Example A1 prepared in Experimental Example 1, 5 parts of titanium oxide (rutile type titanium oxide manufactured by Ishihara Sangyo Co., Ltd., trade name "TIPAQUE CR-95", average particle diameter 280 nm), 45 parts of calcium carbonate (manufactured by Shiraishi Calcium Co., Ltd., trade name "Softon 3200"), 1 part of a dispersant (manufactured by BYK, trade name "DISPERBYK-2015"), 1 part of an antifoaming agent (manufactured by Kusumoto Chemicals, Ltd., trade name "DISPARLON AQ7533"), and 1.5 parts of a thixotropic agent (manufactured by BYK, trade name "OPTIGEL WX") were added per 100 parts of the acrylic polymer contained in the composition, and further water was added to adjust the solid content to 50%. Thus, the acrylic coating composition according to this example was obtained.
[0099] (Examples B2, B12) Acrylic coating compositions according to each example were obtained in the same manner as in Example B1, except that the amounts of calcium carbonate, dispersant, and thixotropic agent used were as shown in Table 2.
[0100] (Examples B3 to B7) Acrylic coating compositions according to each example were obtained in the same manner as in Example B2, except that a thickener of the type and amount shown in Table 2 was further added.
[0101] (Example B8~B11) Each example of acrylic coating composition was obtained in the same manner as in Example B2, except that the types and amounts of thickeners shown in Table 2 were further added and thixotropic agents were not used.
[0102] (Examples B13, B14) Each acrylic coating composition was obtained in the same manner as in Example B1, except that the types and amounts of thickeners shown in Table 2 were added and thixotropic agents were not used.
[0103] The contents of the thickening agents indicated by abbreviations in Table 2 are as follows: H-3300VF: Manufactured by BYK Corporation, product name "RHEOBYK-H 3300VF" T1010: Manufactured by BYK, product name "RHEOBYK-T 1010" L1400: Manufactured by BYK, product name "RHEOBYK-L 1400" SANHEC-L: Manufactured by Sansho Co., Ltd., product name "SANHEC L" WSR N-80: Manufactured by Dow Chemical, product name "POLYOX WSR N-80" UH-450VF: Manufactured by ADEKA Corporation, product name "ADEKA NOL UH-450VF" UH-420: Manufactured by ADEKA Corporation, product name "ADEKA NOL UH-420"
[0104] <Measurement and Evaluation> The following measurements and evaluations were performed on the coating compositions related to Examples B1 to B14 and the coating composition of Example A1. The results are shown in Table 2.
[0105] [Viscosity measurement using a BH-type viscometer] Viscosity was measured at 30°C using a BH-type viscometer with a No. 6 rotor at 2 rpm and 20 rpm. From the obtained results, the ratio (Ti value) of the viscosity measured at 2 rpm to the viscosity measured at 2 rpm was calculated.
[0106] [Viscosity measurement using a cone-plate rheometer] Using a Haacke Rheo Stress 1 rheometer viscometer with a cone-type rotor (Cone Diameter: 35mm, Cone Angle: 0.5deg.), the shear rate was measured at 30°C from 0.1 to 2000 sec. -1 From the viscosity when continuously changed, the shear rate 1 sec -1 , 10sec -1 , 100 sec -1 and 1000sec -1 The viscosity was measured.
[0107] Furthermore, when the storage modulus G'(23) of the films formed from the coating compositions of Examples B1, B6, and B13 was measured in the same manner as in Experimental Example 1, the storage modulus G'(23) for Example B1 was 290 MPa, for Example B6 it was 320 MPa, and for Example B13 it was 310 MPa, all of which were within the range of 150 MPa to 1000 MPa. In addition, the storage modulus G'(70) of these films was 1.6 MPa for Example B1, 1.4 MPa for Example B6, and 1.5 MPa for Example B13, all of which were 0.40 MPa or higher.
[0108] [Anti-sagging] A painted steel plate, coated with an acid epoxy crosslinking acrylic paint (manufactured by Kansai Paint Co., Ltd., product name "KINO1210TW"), was held horizontally with the painted surface facing upwards. Under conditions of 23°C, the coating composition for each example was applied to the painted surface of the painted steel plate in a 100 mm wide strip using an applicator manufactured by TP Giken Co., Ltd., to a thickness of 200 μm in terms of solid content (i.e., a wet film thickness of 400 μm). Immediately after application, the painted steel plate was placed vertically and left for 1 minute. The condition of the coating (the composition applied to the painted steel plate) was then visually observed. Based on the results, the sagging resistance was evaluated on the following three levels. A higher score indicates better sagging resistance. 3 points: No sagging or drooping was observed. Points 2: Sagging is observed, but no drooping has occurred. 1 point: Drooping has occurred.
[0109] [Die coating properties] A Nordson SCDM-3 / 140 coating head (120 mm wide) was adjusted to a shim thickness of 300 μm. The coating compositions for each example were dispensed onto the above coating head at a discharge rate of 3000 cm³. 3 The liquid was pumped at a rate of / min. At this time, the width of the liquid film discharged from the 120 mm × 300 μm slit was measured at a position 20 mm below the outlet (downward) of the slit, and the die coating performance was evaluated on the following three levels according to this value. A higher score indicates better die coating performance. If the continuity of the liquid film in the width direction was impaired at a position 20 mm below the outlet (for example, if the liquid film was bifurcated or divided into two or more parts), it was evaluated as 1 point regardless of the overall width. 3. The width of the liquid film at a position 20 mm below the outlet is 100 mm or more. 2. The width of the liquid film is 80 mm or more and less than 100 mm. 1. The width of the liquid film is less than 80 mm.
[0110] [Defoaming] Under conditions of 23°C, 100 ml of the coating composition was placed in a 200 ml beaker, stirred at 1000 rpm for 5 minutes using a disperser, and then allowed to stand for 5 minutes. The liquid level H1 (distance from the bottom of the beaker to the liquid surface; the same applies hereafter) was measured, and the defoaming ability was evaluated on the following three levels based on its relative relationship to the initial (before stirring) liquid level H0. The results are shown in Table 2. A higher score indicates better defoaming ability. 3 points: H1 and H0 remain unchanged (no rise in liquid level) Points 2: H1 is greater than H0, but the difference is less than 10% (liquid level rise of less than 10%). 1 point: H1 is greater than H0 by more than 10% (liquid level rise of more than 10%)
[0111] [Table 2]
[0112] The coating compositions in Examples B1 to B11 all received evaluation scores of 2 or higher for both die-coating properties and defoaming properties. These coating compositions exhibit practical defoaming properties and are suitable for forming protective coating materials on top of coating films by die coating.
[0113] Although specific examples of the present invention have been described in detail above, these are merely illustrative and do not limit the scope of the claims. The technologies described in the claims include various modifications and changes to the specific examples illustrated above. [Industrial applicability]
[0114] The coating protective coating material provided by the technology described in this specification is suitable as a coating protective coating material that is applied to the coating of an object to be protected which has a coating and serves to protect the coating from damage and deterioration such as scratches and dirt, and is used in a manner that it can be peeled off from the object to be protected after it has finished fulfilling its protective role. The object to be protected may be, for example, a painted metal sheet (for example, painted steel sheet used in housing materials, building materials, ships, railway vehicles, automobiles and other transportation equipment), a synthetic resin sheet with a coating, or molded products thereof. The above-mentioned protective coating material can be preferably used to protect an article to be protected (an article having a coating formed by the above coating treatment, such as a metal plate such as a steel plate or a molded product thereof) which has been coated with paints of various compositions, such as acrylic paints, polyester paints, alkyd paints, melamine paints, urethane paints, acid epoxy crosslinked paints, or composites thereof (e.g., acrylic melamine paints, alkyd melamine paints), by being applied to the coating. [Explanation of Symbols]
[0115] 10. Protective coating material for paint film 20 Protected Objects 22 Coating film
Claims
1. A coating film protective coating material formed from an acrylic coating composition containing an acrylic polymer as a base polymer, The monomer component constituting the acrylic polymer is a monomer (m T ) and a monomer (m L ), wherein the monomer (m T ) contains at least acrylonitrile, The monomer (m T ) and the monomer (m L ) molar ratio (m T / m L ) is 0.8 or more and 1.5 or less, A coating film protective coating material having a storage modulus at 23°C of 150 MPa or more and 1000 MPa or less, and a storage modulus at 70°C of 0.40 MPa or more.
2. An acrylic coating composition for forming a coating film protective coating material, comprising: The composition includes an acrylic polymer as a base polymer, The monomer component constituting the acrylic polymer is a monomer (m T ) and a monomer (m L ), wherein the monomer (m T ) contains at least acrylonitrile, The monomer (m T ) and the monomer (m L ) molar ratio (m T / m L ) is 0.8 or more and 1.5 or less, An acrylic coating composition that forms a coating film protective coating material having a storage modulus at 23°C of 150 MPa or more and 1000 MPa or less, and a storage modulus at 70°C of 0.40 MPa or more.
3. The acrylic coating composition according to claim 2, wherein the acrylic polymer has a glass transition temperature of -30°C or higher and -5°C or lower, calculated based on the composition of the monomer components.
4. The acrylic coating composition according to claim 2 or 3, wherein the content of acrylonitrile in the monomer component is greater than 50 mol %.
5. The acrylic coating composition according to claim 2 or 3, further comprising 1 to 60 parts by weight of an inorganic powder based on 100 parts by weight of the acrylic polymer.
6. The acrylic coating composition of claim 5 , wherein the inorganic powder comprises titanium oxide.
7. The acrylic coating composition according to claim 2 or 3, which is a composition in the form of an aqueous emulsion in which the acrylic polymer is dispersed in an aqueous solvent.
8. Viscosity V measured using a BH type viscometer at 2 rpm 1 is 20 Pa·s or more and 200 Pa·s or less, and Shear rate measured by cone-plate rheometer: 100 sec -1 Viscosity at V 2 The acrylic coating composition according to claim 2 or 3, wherein the viscosity is 1.0 Pa·s or more.
9. Providing an acrylic coating composition comprising an acrylic polymer as a base polymer; applying the acrylic coating composition onto a coating of an object to be protected; and drying the acrylic coating composition to form a coating film protective coating material that temporarily protects the coating film; Including, The monomer component constituting the acrylic polymer is a monomer (m T ) and a monomer (m L ), wherein the monomer (m T ) contains at least acrylonitrile, The monomer (m T ) and the monomer (m L ) molar ratio (m T / m L ) is 0.8 or more and 1.5 or less.
10. The method for protecting a coating according to claim 9, wherein the acrylic coating composition is applied by a slot die.